People like green shirts better♀️
X=-2→y=7(6)^(-2+2)+1=7(6)^0+1=7(1)+1=7+1→y=8; (x,y)=(-2,8)
x=-5→y=7(6)^(-5+2)+1=7(6)^(-3)+1=7/6^3+1=7/216+1=0.0324+1→y=1.0324→(x,y)=(-5,1.0324)
Answer: Graph 3
I believe the answer is 2(15t).
Answer:
The end behavior of a function f describes the behavior of the graph of the function at the "ends" of the x-axis. In other words, the end behavior of a function describes the trend of the graph if we look to the right end of the x-axis (as x approaches +∞ ) and to the left end of the x-axis (as x approaches −∞ ).